Biotechnological substances from fungi - Häder, Donat-Peter (Natural Bioactive Compounds, 2020)
Fungi are a rich source of secondary metabolites that offer a plethora of valuable substances for pharmacology, medicine, food, and fodder production. Biotechnological exploitation of fungi has long been known in the production of tea. Starting with Fleming’s discovery of penicillin, a large number of antibiotics has been isolated mainly from ascomycete molds and further modified chemically. These substances are directed against pathogenic bacteria and affect cell wall and protein biosynthesis. Problems are caused by dormant stages of bacteria and multiresistant strains. Fungi are used to produce biotechnologically important substances such as peptides, enzymes, and growth factors from agricultural waste by hydrolytic enzymes. In addition, biosurfactants, bioactive peptides, and medical important drugs such as hypercholesterolemic, antihypertensive, and antitumor agents as well as antioxidants are being produced.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Antibiotics; Bacterial cell wall; Fermentation; Food production; Fungi; Pharmaceuticals; Protein biosynthesis